2009
DOI: 10.1002/jlcr.1673
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐14 labeled methyl 2‐chloro‐2‐oxoacetate: a convenient carbon‐14 labeled oxalyl chloride equivalent

Abstract: Oxalyl chloride is a versatile two‐carbon building block for synthesizing organic molecules. Carbon‐14 labeled oxalyl chloride should be a useful reagent for labeling many of these compounds. Unfortunately, its preparation suffers from low radiochemical yield and problems with stability, isolation and analysis. Because of these issues, the reagent is not a convenient or practical carbon‐14 label source. Synthetically, methyl 2‐chloro‐2‐oxoacetate reacts as an oxalyl chloride equivalent. This report describes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Burrell et al reported a synthesis of 14 C 2 labelled methyl 2-chloro-2-oxoacetate as a convenient labelled oxalyl chloride equivalent by means of selective partial hydrolysis of labelled dimethyl oxalate, and showed its synthetic utility in the synthesis of 14 C 2 labelled dichloropyrazinones. 12 Elaboration of this chemistry provided a simple, high yielding route to unsymmetrical 13 C deuterated or perdeuterated oxalates. This method not only prevents the formation of mixtures but also allows the stepwise introduction of 13 C or deuterium labels at different positions within the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Burrell et al reported a synthesis of 14 C 2 labelled methyl 2-chloro-2-oxoacetate as a convenient labelled oxalyl chloride equivalent by means of selective partial hydrolysis of labelled dimethyl oxalate, and showed its synthetic utility in the synthesis of 14 C 2 labelled dichloropyrazinones. 12 Elaboration of this chemistry provided a simple, high yielding route to unsymmetrical 13 C deuterated or perdeuterated oxalates. This method not only prevents the formation of mixtures but also allows the stepwise introduction of 13 C or deuterium labels at different positions within the molecule.…”
Section: Resultsmentioning
confidence: 99%